Whey Peptide–Based Formulas With ω-3 Fatty Acids Are Protective in Lipopolysaccharide-Mediated Sepsis. (July 2015) - Tsutsumi, Rie; Horikawa, Yousuke T.; Kume, Katsuyoshi; Tanaka, Katsuya; Kasai, Asuka; Kadota, Takako; Tsutsumi, Yasuo M.
Background: Sepsis and septic shock syndrome are among the leading causes of death in critically ill patients. Lipopolysaccharide (LPS) released by bacteria within the colon may translocate across a compromised epithelium, leading to oxidative stress, inflammation, sepsis, and eventually death. Methods : We examined the effects of a whey-based enteral formula high in cysteine (antioxidant precursor) and the addition of ω-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), against a mouse model of LPS-induced sepsis. Mice were fed either a whey-based diet with EPA-DHA (PAF), a whey-based diet without EPA-DHA (PSTD), or a casein-based control diet (CONT). Results : Mice fed PAF or PSTD were protected against LPS-induced weight loss. Whey-based diets suppressed inflammatory cytokine release and oxidative stress damage. Furthermore, PAF and PSTD were able to inhibit autophagy, a mechanism in which the cell recycles damaged organelles. These anti-inflammatory and antioxidative effects of PSTD and PAF resulted in decreased liver inflammation and intestinal damage and promoted protective microbiota within the intestines. Conclusions : These data suggest a clinical role for whey peptide–based diets in promoting healing and recovery in critically ill patients.